Novel technique for intraoperative sciatic nerve assessment in complex primary total hip arthroplasty: a pilot study. Issue 2 (March 2018) - Shemesh, Shai S.; Robinson, Jonathan; Overley, Samuel; Bronson, Michael J.; Moucha, Calin S.; Chen, Darwin
Introduction: Sciatic nerve injury (SNI) is a potentially devastating complication after total hip arthroplasty (THA). Intraoperative neural monitoring has been found in several studies to be useful in preventing SNI, but can be difficult to implement. In this study, we examine the results of using a handheld nerve stimulator for intraoperative sciatic nerve (SN) monitoring during complex THA requiring limb lengthening and/or significant manipulation of the SN. Methods: A consecutive series of 11 cases (9 patients, 11 hips) with either severe developmental dysplasia of the hip (Crowe 3-4) or other underlying conditions requiring complex hip reconstruction involving significant leg lengthening and/or nerve manipulation. SN function was monitored intraoperatively by obtaining pre- and post-reduction thresholds during component trialing. The results of nerve stimulation were then used to influence intraoperative decision-making. Results: No permanent postoperative SN complications occurred, with an average increase of 28.5 mm in limb length, range (6-51 mm). In 2 out of 11 cases, a change in nerve response was identified after trial reduction, which resulted in an alternate surgical plan (femoral shortening osteotomy and downsizing femoral head). In the remaining cases, the stimulator demonstrated a response consistent with the baseline assessment, assuring that the appropriate lengthening was achieved without SNI. 1 patient had a transient motor and sensory peroneal nerve palsy, which resolved within 2 weeks. Conclusions: The intraoperative use of a handheld nerve stimulator facilitates surgical decision-making and can potentially prevent SNI. The real-time assessment of nerve function allows immediate corrective action to be taken before nerve injury occurs.